DETERMINANTS OF FINANCIAL BEHAVIOUR OF MICRO, SMALL AND MEDIUM-SIZE ENTERPRISES OWNER IN INDONESIA (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
Economic activities of MSMEs in Indonesia are on the rise after pandemic. Non-cash payment systems are more attractive to consumers and producers. The non-cash payment system in the form of QRIS is increasingly being used in business transactions. Therefore, this study aims to analyze the determinants of financial behavior of MSME owners who use QRIS. This research used sample technique purposive sampling and proportional random sampling. A total of 204, respondents are small micro business owners who use QRIS from Medan, Makassar and Bali. The research instrument used a questionnaire distributed to MSME owners. The determining variables used are age, length of business, education, and religion of business owners. The data analysis technique uses multiple linear regression with SPSS tools. The results showed that education has an impact on the financial behavior of QRIS-using MSMEs, while age, religion, region, and length of business have no impact on financial behavior.
Keywords: Financial Behavior; QRIS; MSMEs